Bio‐organic soil amendment promotes the suppression of Ralstonia solanacearum by inducing changes in the functionality and composition of rhizosphere bacterial communities. Issue 4 (8th June 2022) - Deng, Xuhui; Zhang, Na; Li, Yuchan; Zhu, Chengzhi; Qu, Baoyuan; Liu, Hongjun; Li, Rong; Bai, Yang; Shen, Qirong; Falcao Salles, Joana
Summary: Stimulating the development of soil suppressiveness against certain pathogens represents a sustainable solution toward reducing pesticide use in agriculture. However, understanding the dynamics of suppressiveness and the mechanisms leading to pathogen control remain largely elusive. Here, we investigated the mechanisms used by the rhizosphere microbiome induces bacterial wilt disease suppression in a long‐term field experiment where continuous application of bio‐organic fertilizers (BFs) triggered disease suppressiveness when compared to chemical fertilizer application. We further demonstrated in a glasshouse experiment that the suppressiveness of the rhizosphere bacterial communities was triggered mainly by changes in community composition rather than only by the abundance of the introduced biocontrol strain. Metagenomics approaches revealed that members of the families Sphingomonadaceae and Xanthomonadaceae with the ability to produce secondary metabolites were enriched in the BF plant rhizosphere but only upon pathogen invasion. We experimentally validated this observation by inoculating bacterial isolates belonging to the families Sphingomonadaceae and Xanthomonadaceae into conducive soil, which led to a significant reduction in pathogen abundance and increase in nonribosomal peptide synthetase gene abundance. We conclude that priming of the soil microbiome with BF amendment fostered reactive bacterial communities in the rhizosphere of tomato plants in response to biotic disturbance.